(3CcGOjejI GdHMK GdYdei h GdJcfhdhLjG GdegGe h GdechfGJs - (3CcGOejI GdHMK GdYdei h GdJcfhdhLjG(B.s; (3CcGOjejI GdHMK GdYdei h GdJcfhdhLjG(B.s ((3GdbGgQI (B:s (3CcGOjejI GdHMK GdYdei h GdJcfhdhLjG(B,s, 1996)
(3jJfGhd GdcJGH GdJYQa Ydi CcGOejI GdHMK GdYdei h GdJcfhdhLjG h GdJYQja HegGegG(B.s
(3JYQja CcGOejI GdHMK GdYdei h GdJcfhdhLjG(B.s
All age.
Keywords: (3CcGOejI GdHMK GdYdei(B.s